Locus of control of male adolescents with imprisoned fathers its relation to their academic adjustment - Bataan, Arminda A .; Losare, Anna Marie C. . (2002.)
This study sought to determine the kind of locus of control of the respondents and the level of academic adjustment as seen in their grade point averages. The researches aimed to find out if there exists a relationship between locus of control and academic adjustment of these male adolescents with imprisoned fathers. This study was patterned on a previous research on the relationship between the same variables but this study utilized a different instrument and respondents came from Iloilo province., Fifteen (15) college students whose fathers were imprisoned at the time that they were enrolled served as respondents of the study. All respondents came from Iloilo, 33% of which are from Iloilo City and the remaining 67% are from the municipalities. Their ages range from 17-24. Respondents were selected using the snowball method. Respondents were asked to answer the Trice Academic Locus of Control Scale. the scale is composed of 28 items answerable by true or false determined the kind of locus of control of these male adolescents with imprisoned fathers. In addition, the repondents were asked to submit their copy of grades of the previous semester to determine how well they adjust academically. The computed Pearson Product Moment Correlation is r=0.26 with a rcrit=0.441 at 0.05 alpha. This signifies that indeed there is a significant relationship between locus of control and academic adjustment of male adolescents with imprisoned fathers. However, it revealed a weak positive correlation between locus of control and academic adjustment. The findings imply that locus of control is not the sole cause or factor for academic adjustment. The cause or source of a well-adjusted academic performance of male adolescents with imprisoned fathers may therefore be attributed to other factors such as economic and social support coming from family and friends. Such factors could even lead to a poor academic performance. Lastly, academic adjustment and locus of control vary among the respondents, which suggest individual diffeences among them.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Adolescent psychology